The Influence of Family Harmony and School Environment on Sociology Learning Achievement in Senior High School Students - Nismawati Nismawati; Cahyadi Nugroho; Sumitro Sumitro (STKIP Yapis Dompu, 2023)
This research is verification research or descriptive research. The investigated variables are family harmony (X1), school environment (X2) and students learning achievements (Y). The research was conducted at SMAN 4 Barru District with 105 students as the samples from 144 students as the populations. The samples werw taken through propotional and random sampling procedure. The data were collected by employing questionnaires, test and documentation. The hypothesis was tested and analyzed by using simple regression and double regression. The results of the research reveal that (1) There is positive influence and significant influence of family harmony on Sociology learning achievements of IPS students at SMA Negeri 4 Barru, (2) There is positive influence and significant influence of school environment on Sociology learning achievements of IPS students at SMAN 4 Barru, and (3) There is positive and significant influence between family harmony and school environment simultaneously on learning achievements of the IPS students at SMAN 4 Barru.